Incarceration and exposure to internally displaced persons camps associated with reproductive rights abuses among sex workers in northern Uganda - Birungi, Josephine; Erickson, Margaret; Goldenberg, Shira M.; Akello, Monica; Shannon, Kate; Nguyen, Paul; Muzaaya, Godfrey (BMJ, 2017)
While female sex workers (FSWs) face a high burden of violence and criminalisation, coupled with low access to safe, non-coercive care, little is known about such experiences among FSWs in conflict-affected settings, particularly as they relate to sexual and reproductive health (SRH) and rights. We explored factors associated with lifetime abortions among FSWs in northern Uganda; and separately modelled the independent effect of lifetime exposures to incarceration and living in internally displaced persons (IDP) camps on coerced and unsafe abortions. Methods Analyses are based on a community- based cross-sectional research project in Gulu District, northern Uganda (2011–2012) with The AIDS Support Organization (TASO) Gulu, FSWs, and other community organisations. We conducted questionnaires, sex worker/ community-led outreach to sex work venues, and voluntary HIV testing by TASO. Results Of 400 FSWs, 62 had ever accessed an abortion. In a multivariable model, gendered violence, both childhood mistreatment/or abuse at home [adjusted odds ratio (AOR) 1.96; 95% confidence interval (95% CI) 0.99–3.90] and workplace violence by clients (AOR 3.57; 95% CI 1.31–9.72) were linked to increased experiences of abortion. Lifetime exposure to incarceration retained an independent effect on increased odds of coerced abortion (AOR 5.16; 95% CI 1.39–19.11), and living in IDP camps was positively associated with unsafe abortion (AOR 4.71; 95% CI 1.42–15.61). Discussion and conclusions These results suggest a critical need for removal of legal and social barriers to realising the SRH rights of all women, and ensuring safe, voluntary access to reproductive choice for marginalised and criminalised populations of FSWs.
Keywords: Reproductive rights; Sex workers; Northern Uganda